(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The article presents specialized software methods for reducing stress concentration. Objects of study are cylindrical test specimens subjected to axial loading. Notching with different shapes and sizes on the specimens were formed to reduce the stresses in the endangered areas. The geometric parameters of notches identified through the specialized built-in modules to the ANSYS software. An analysis performed were to show the influence of stresses acting on the fatigue limit during different cycles. The results of the study were present in a graphical form.